Research of Technological Test of Enhanced Shot-peening for Carburized Gear Steel - Zhang Yuanyuan; Yang Liu; Chen Lihui (Jixie chuandong)
Based on shot-peening hardness tests performed on carburized gear steel,the hardness effectiveness of shot-peening on tooth flank and root is studied,it is aimed to find out the factors and parameters which are related to surface roughness in different shot-peening process parameters,so that rational parameter combination of enhanced shot-peening can be available to provide guidance to enhanced shot-peening on other parts.